2020
DOI: 10.3389/fpls.2019.01686
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Into N-Glycan Fucosylation and Core Xylosylation in C. reinhardtii

Abstract: Chlamydomonas reinhardtii (C. reinhardtii) N-glycans carry plant typical b1,2-core xylose, a1,3-fucose residues, as well as plant atypical terminal b1,4-xylose and methylated mannoses. In a recent study, XylT1A was shown to act as core xylosyltransferase, whereby its action was of importance for an inhibition of excessive Man1A dependent trimming. N-Glycans found in a XylT1A/Man1A double mutant carried core xylose residues, suggesting the existence of a second core xylosyltransferase in C. reinhardtii. To furt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…In microalgae, current knowledge regarding the N-glycosylation processes is available essentially in species belonging to the Chlorophytes (Table 1). Among these, the Chlorophyceae Chlamydomonas reinhardtii and the Trebouxiophycea Chlorella vulgaris have been the most investigated microalgae so far (Mathieu-Rivet et al, 2013;Vanier et al, 2017;Lucas et al, 2018Lucas et al, , 2020Schulze et al, 2018;Mócsai et al, 2019Mócsai et al, , 2020aOltmanns et al, 2020). Concerning microalgae with secondary plastids, the structural data available regarding N-glycans have been obtained from the diatom Phaeodactylum tricornutum (Baïet et al, 2011;Vanier et al, 2015;Lucas et al, 2018) and from the Euglenoid Euglena gracilis (De La Canal and Parodi, 1985;O'Neill et al, 2017).…”
Section: N-glycosylation Pathways In Microalgaementioning
confidence: 99%
See 2 more Smart Citations
“…In microalgae, current knowledge regarding the N-glycosylation processes is available essentially in species belonging to the Chlorophytes (Table 1). Among these, the Chlorophyceae Chlamydomonas reinhardtii and the Trebouxiophycea Chlorella vulgaris have been the most investigated microalgae so far (Mathieu-Rivet et al, 2013;Vanier et al, 2017;Lucas et al, 2018Lucas et al, , 2020Schulze et al, 2018;Mócsai et al, 2019Mócsai et al, , 2020aOltmanns et al, 2020). Concerning microalgae with secondary plastids, the structural data available regarding N-glycans have been obtained from the diatom Phaeodactylum tricornutum (Baïet et al, 2011;Vanier et al, 2015;Lucas et al, 2018) and from the Euglenoid Euglena gracilis (De La Canal and Parodi, 1985;O'Neill et al, 2017).…”
Section: N-glycosylation Pathways In Microalgaementioning
confidence: 99%
“…Thus, glycoproteins harboring the non-canonical Man 5 GlcNAc 2 are submitted in the Golgi apparatus to the action of glycosyltransferases responsible for the addition of decorations. Mass spectrometry analyses carried out on C. reinhardtii secreted and membrane-bound proteins have shown that mature N-glycans are partially O-methylated Man 3 GlcNAc 2 to Man 5 GlcNAc 2 substituted by one or two Xyl residues (Mathieu-Rivet et al, 2013), and for a minor part by one fucose residue (Oltmanns et al, 2020). Recently, Schulze et al (2018) and Lucas et al (2020) have showed that the first Xyl is linked in β(1,2) to the β-Man via the action of the xylosyltransferase A (XylTA) similarly to the plant xylosylation process.…”
Section: Gnt I: To Have or Not To Havementioning
confidence: 99%
See 1 more Smart Citation
“…In order to assign glycopeptides, samples were measured employing In-Source collision induced dissociation (IS-CID) as described previously followed by analysis of data with Ursgal and SugarPy (Kremer et al, 2016;Oltmanns et al, 2020;Schulze et al, 2020).…”
Section: Mass Spectrometry Measurementsmentioning
confidence: 99%
“…In land plants, Golgi maturation leads to N-glycans modified with β1,2-core xylose and α1,3-core fucose (Strasser, 2016). In Chlamydomonas reinhardtii, a unicellular biflagellate green alga, N-glycans can be decorated with core xylose and -fucose (Lucas et al, 2020;Oltmanns et al, 2020;Schulze et al, 2018). Additionally, 6O-methylation of mannose and addition of a terminally linked β1,4-xylose were reported (Mathieu-Rivet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%